'An Analysis of U.S. Fiscal and Generational Imbalances : Who Will Pay and How?' - Batini, Nicoletta (IMF Working Papers; Working Paper ;, 2011)
This paper updates existing measures of the U.S. fiscal gap to include federal laws up to and including the mid-December 2010 federal fiscal stimulus. It then applies the methodology of generational accounting to establish how the burden of adjustment required to attain fiscal sustainability is shared across generations. We find that the U.S. fiscal and generational imbalances are large under plausible parametric assumptions, and, while not much affected by the financial crisis, they have not improved much by the passing of the Final Healthcare Legislation. We find that, under our baseline scenario, a full elimination of the fiscal and generational imbalances would require all taxes to go up and all transfers to be cut immediately and permanently by 35 percent. A delay in the adjustment makes it more costly.